(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of single stage arthroscopically assisted reconstruction of multiligamentous knee injury (MLKI) with autografts. Methods: This descriptive study was conducted in Orthopaedic Department Liaquat National Hospital and Medical College Karachi from 21st January 2017 to 21st January 2022.All adults’ patients with multiligamentous knee injury (MLKI) fulfilling the inclusion criteria were treated with arthroscopically assisted single stage surgery utilizing Hamstring and Quadriceps tendon autografts. Post operative functional outcome was assessed with International Knee Documentation Committee scores (IKDC) and Tegner-Lysholm score at six months, one year and two years follow up. The pre surgery and post-surgery IKDC and Tegner-Lysholm scores were compared and P value was calculated with paired sample-t test. P value <0.05 was considered significant. Results: We operated 35 patients with MLKI. The mean age was 31.62±6.89 years. All the patients were males. Right MLKI was present in 22(62.85%) and left in 13(37.14%). The predominant patterns of MLKI were Anterior cruciate ligament(ACL) and Medial collateral ligament(MCL) tear in 9(25.71% ) patients and ACL,PCL and posterolateral corner (PLC) tear in 7(20%) patients. The pre operative mean IKDC score was 39.34±22. At six months the score was 52.34±21,at one year 72.23±10 and at two years 87.88±55.(P<0.05).At two years follow the Tegner-Lysholm score was with excellent in 06( 17.14%) patients, good in 26( 74.28%) and fair in 03( 8.57%) patients(P<0.05). Conclusion: Excellent and good functional outcome was achieved with single stage arthroscopically assisted reconstruction of multiligamentous knee injury using autografts.